The Effect of Drug Swallowing Supervisor Assistance in Improving the Compliance of Drug-Taking Tb Patients in Rantau Prapat in 2021 - Manurung, Nixson; Tanjung, Ahmad Marzuki (Jurnal Media Informatika, 2024)
Tuberculosis is still a global and national public health problem. According to a 2014 WHO report, at the global level, it is estimated that 9.6 million new TB cases will be reported. Official report from the TB Sub-Directorate of the Ministry of Health of the Republic of Indonesia based on the 2014 WHO Report: In Indonesia, it is estimated that there are 1 million new TB cases (399 per 100,000 population) with 100,000 deaths (41 per 100,000 population). The purpose of this study is to determine the effect of drug swallowing supervisor assistance (PMO) in increasing the compliance of TB patients in taking medication in Rantau Prapat. The design of this study uses an analytical observation research method. The population in this study is all TB patients in the Labuhan Batu area which totals 967 people. The sample in this study is TB patients in Labuhan Batu, Rantau Prapat with a total of 15 TB patients. The results of the study showed that of the 9 clients (60%) who received good family support, 7 clients (46.7%) behaved well in preventing the transmission of pulmonary TB and 2 clients (13.3%) behaved poorly in the prevention of pulmonary TB transmission. The results of the study were analyzed using the chi-square test to determine decision-making on the hypothesis tested. The working hypothesis raised is based on Ha, namely there is a relationship between PMO support and patient compliance in taking medication by pulmonary TB clients The results of statistical analysis using the chi-square test obtained a p value = 0.041, then it can be concluded that Ho is rejected. The conclusion of this study is that there is a relationship between PMO support and compliance of TB patients in taking medication.